2000
DOI: 10.1562/0031-8655(2000)072<0652:iourof>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of UV Radiation on Four Freshwater Invertebrates¶

Abstract: Laboratory tests confirmed a negative and variable response of the following four species to artificial UV radiation: Cypridopsis vidua, an ostracode; Chironomus riparius, a midge larvae; Hyalella azteca, an amphipod; and Daphnia magna, a daphnid. Severe damage occurred at UV-B irradiance ranging from 50 to 80% of incident summer values. Under constant exposure to UV and photosynthetically active radiation (PAR) the acute lethal response was recorded at 0.3, 0.8, 0.8 and 4.9 W m-2 UV-B for D. magna, H. azteca,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 21 publications
1
11
1
1
Order By: Relevance
“…Divergence from the reciprocity law was observed in aquatic animals under UVB radiation at low intensity such as 0.2-0.4 W m −2 (Cywinska et al, 2000;Wübben, 2000), suggesting a presence of damage threshold by UVB intensity. In contrast, reciprocity was applicable to mortality of T. urticae eggs even if those were exposed to very low-intensity UVB radiation (0.014-0.023 W m −2 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Divergence from the reciprocity law was observed in aquatic animals under UVB radiation at low intensity such as 0.2-0.4 W m −2 (Cywinska et al, 2000;Wübben, 2000), suggesting a presence of damage threshold by UVB intensity. In contrast, reciprocity was applicable to mortality of T. urticae eggs even if those were exposed to very low-intensity UVB radiation (0.014-0.023 W m −2 ).…”
Section: Discussionmentioning
confidence: 93%
“…However, mortality of shrimp zoea after UVB irradiation at low intensity (0.2 W m −2 ) diverged from the reciprocity law, which had been upheld under radiation at higher irradiances (Wübben, 2000). Similar divergence from reciprocity in UVB damage was also found for several cases of aquatic animals (Cywinska et al, 2000). Therefore, applicability of the reciprocity law to UV damage in organisms is still disputable.…”
Section: Introductionmentioning
confidence: 84%
“…1a). This active habitat selection of gammarids is most likely explained by the potential of UV-B irradiation to induce acute toxicity towards macroinvertebrates (in terms of damaged cells and tissues; Obermüller et al, 2007), observed even at intensities as low as 0.8 W/m 2 (Cywinska et al, 2000). As the present study used a comparable UV-B-intensity (i.e.…”
Section: (In)direct Effects Of Ambient Uv-irradiation and Nano-tio 2 mentioning
confidence: 88%
“…A depletion of the stratospheric ozone layer, as expected under many climate change scenarios, will increase the exposure to damaging radiation. The freshwater ostracods Heterocypris incongruens and Cypridopsis vidua (Mü ller) are highly tolerant to UV-B radiation (Hurtubise, Havel &Little, 1998 andCywinska, Crump &Lean, 2000;respectively), and preliminary experiments with E. virens indicated that its greenly pigmented valves provide protection against UV (Van den Broecke, Schö n & Martens, 2007).…”
Section: Uv-b Radiationmentioning
confidence: 99%